Establishing Semantok Reservoir Operation Rules to Obtain the Highest Crop Intensity in Semantok Irrigation Area - Rizky Ramadhani Anwar Santosa; Endita Prima Ari Pratiwi; Istiarto (Postgraduate, University of Mataram, 2025)
The Indonesian government is improving food security by building water infrastructure, including 61 dams for agricultural irrigation. Semantok Dam, one of these projects, serves Daerah Irigasi (D.I.) Semantok (1906 ha). However, long‐term inflow data is still lacking and the reservoir operation rules are still under development. This research aims to develop Semantok reservoir operating rules to maximize cropping intensity. Rainfall‐runoff simulation was conducted using the F.J. Mock method. Calibration (2017–2019) and verification (2020–2023) resulted in optimal parameters with minimum volume error, which were then applied to full‐period F.J. Mock simulations (1999–2023). The resulting simulated inflows was used to calculate irrigation water requirements using the Net Field Requirements method for two cropping patterns: double cropping of rice‐secondary crops and quadruple cropping onion. The reservoir operating rules were optimized for wet, normal, and dry years (probability exceeding 35%, 50%, and 65%). This study examined cropping intensity under various hydrological conditions. Cropping Pattern (CP) I achieved 300%, 281%, and 242%, while CP II achieved 400%, 400%, and 374% in wet, normal, and dry years, respectively. Future research should optimize water allocation at the sub D.I. level to improve irrigation efficiency and agricultural profitability.